BRIDGE TO THE FUTURE BETWEEN SCIENCE AND PRODUCTION (FOLLOWING THE RESULTS OF THE 21-TH INTERNATIONAL SCIENTIFIC CONFERENCE «FOUNDRY AND METALLURGY 2013. BELARUS») - D. M. Kukuj (Литьë и металлургия, 2013)
The general description of the current state of foundry production of Belarus is given.